2011
DOI: 10.1139/e11-015
|View full text |Cite
|
Sign up to set email alerts
|

The quest for chron E23r at Partridge Island, Bay of Fundy, Canada: CAMP emplacement postdates the end-Triassic extinction event at the North American craton

Abstract: The Partridge Island stratigraphic section at the Bay of Fundy, Maritime Canada, reveals a continental sedimentary succession with the end-Triassic mass extinction level closely followed by basalts of the Central Atlantic Magmatic Province (CAMP). New Paleomagnetic data show that a short reverse magnetic polarity chron, correlative to E23r of the Newark Geomagnetic Polarity Time Scale (GPTS), is present below the extinction event. Organic carbon isotope data and basalt geochemistry further indicate that the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…But the correlation between the strata themselves or the extinction event has not appreciably changed, except that the extinction level and hence the Partridge Island Member are now late Rhaetian in age by definition. Deenen et al (2011) found the reverse polarity chron E23r, first identified in the Newark basin (Kent et al 1995), at the type section at Partridge Island below the palynological extinction level (Fig. A5).…”
Section: Partridge Island Member Of the Blomidon Formationmentioning
confidence: 71%
See 2 more Smart Citations
“…But the correlation between the strata themselves or the extinction event has not appreciably changed, except that the extinction level and hence the Partridge Island Member are now late Rhaetian in age by definition. Deenen et al (2011) found the reverse polarity chron E23r, first identified in the Newark basin (Kent et al 1995), at the type section at Partridge Island below the palynological extinction level (Fig. A5).…”
Section: Partridge Island Member Of the Blomidon Formationmentioning
confidence: 71%
“…Based on zircon U-Pb dates, the age of the Partridge Island Member is latest Rhaetian at 201.564±0.015 Ma (Blackburn et al 2013). Although Olsen (1997) and Olsen et al (2005a, b) interpreted the Partridge Island Member as comprising the base of TS IV, it rests conformably on the underlying Blomidon Formation (contra Kozur and Weems 2010) as shown by the position of E23r (Deenen et al 2011) (see . .…”
Section: White Water Membermentioning
confidence: 98%
See 1 more Smart Citation
“…USA (Kent and Olsen, 1999;Knight et al, 2004;Deenen et al, 2010;Deenen et al, 2011;Font et al, 2011).…”
Section: Accepted Manuscriptunclassified
“…Paleomagnetic data of the CAMP relics are well documented in North America Olsen, 1999,2008;Donohoo-Hurley et al, 2010;Deenen et al, 2011) , Morocco Ortas et al, 2006;Font et al, 2011;Ruiz-Martinez et al, 2012) and South America (de Min et al, 2003;Ernesto et al, 2003), but are still poorly constrained in Iberia. Actually, the sole reliable paleomagnetic pole comes from the Messejana dyke (Ortas et al, 2006), a giant dolerite intrusion that obliquely cuts across the South Portuguese, Ossa-Morena and Central Iberian zones of the Variscan Iberian Massif for more than 530 km .…”
Section: Introductionmentioning
confidence: 99%